2015
DOI: 10.4025/actasciagron.v37i2.19425
|View full text |Cite
|
Sign up to set email alerts
|

<b>‘Desiccation tolerance of <i>Rhamnidium elaeocarpum</i> Reissek (Rhamnaceae) seeds

Abstract: ABSTRACT. This study aimed to investigate the desiccation tolerance of Rhamnidium elaeocarpum Reissek seeds through physiological and biochemical alterations. Fruit were collected from the municipality of Jaupaci, Goias State, Brazil, when the water content of their seeds had a 37% wet basis (w.b.) and the seeds were subsequently kept in a drying oven with air circulation at a temperature of 35ºC until a water content was reached of 20 to 12% (w.b.). The following parameters were evaluated: germination, germin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…These results are in accordance with those of Mohamed & Abdel -Hamid (2013).These new protein bands may be the HSPs or the enzyme of the antioxidant systems which plays very important role in providing tolerance against oxidative burst which is in conformity with the observation made by Singh & Khurana (2016). Another approach to understand the molecular basis of heat stress tolerance is to identify stress induced changes in the protein expression (Bita &Gerats, 2013 andSilva et al 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are in accordance with those of Mohamed & Abdel -Hamid (2013).These new protein bands may be the HSPs or the enzyme of the antioxidant systems which plays very important role in providing tolerance against oxidative burst which is in conformity with the observation made by Singh & Khurana (2016). Another approach to understand the molecular basis of heat stress tolerance is to identify stress induced changes in the protein expression (Bita &Gerats, 2013 andSilva et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…One band which has Rf 0.02 was present in all treatments (monomorphic bands). In addition, two unique bands were detected in the tolerant genotype (Giza 92) under heat stress treatment (Silva et al, 2015) Three types of modifications are observed in the protein patterns of two organs of Vicia faba cv. Assuit 95/2 and Zea maize cv.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CAT enzymatic expression was higher for seeds with a 3 mm radicle (Figure 3), indicating higher oxidative stress. Silva et al (2015) concluded that the presence of CAT might be associated with the acquisition of desiccation tolerance in Rhamnidium elaeocarpum seeds. Their results indicated an increase in the content Acta Scientiarum.…”
Section: Resultsmentioning
confidence: 99%